CRITICAL ANALYSIS OF PATIENT ADVOCACY IN NURSING AND SOCIAL SERVICES AND EVALUATING EFFECTIVENESS, ETHICAL CONSIDERATIONS, AND LEGAL IMPLICATIONS IN ADVOCATING FOR PATIENTS’ RIGHTS AND WELL-BEING - Nadih Abdulrahman Albreet, ‏Kholud Hmoud Abdullah Alonazi, ‏Hana Hail Abdulrahman Aldqmani, ‏Manal Nazal Al Otaiby, Warda Saad Zayed Almotery, Sultan Abdulrahman O Alwani, Fatema Yahya Abdalla Aleyady, Youssef Mohamed Alajmi, (Chelonian Research Foundation, 2022)
Patient advocacy is one of the important concepts of healthcare, which means defending the rights of patients, ensuring their welfare, and giving them high-quality treatment. The essential purpose of this paper is to investigate the performance, ethical aspects, and legal considerations of patient advocacy in the professions of nursing and social services. Results: This paper attempts to impart insights into the problems and chances with which patient advocacy is dealt with by working through all these: literature, methods, results, and discussion. Patient Propositions are given in the light of enthusiastic patient- advocacy so that the outcomes of the patients' health care can be enhanced. Keywords: service delivery, patient advocacy, nursing, social services, cost-effectiveness, ethical concerns, and juridical implications.